Sex‐dependent reductions in high molecular weight adiponectin during acute hyperinsulinemia are prevented with endurance training in older females. (2nd March 2018) - Consitt, Leslie A.; Saxena, Gunjan; Schaefer, Megan
Summary: Objective: The high molecular weight (HMW) adiponectin isoform is considered the active form of adiponectin and is linked to insulin sensitivity and the reduced risk of developing cardiovascular disease. The purpose of the first study was to determine the effects of age and sex on the plasma HMW adiponectin response to acute hyperinsulinemia, and secondly determine whether either endurance or resistance exercise training could affect this response. Design and Participants: Twenty‐six healthy males (19‐84 years) and twenty‐six healthy females (18‐76 years) were recruited and matched for BMI to examine the effects of sex and age on the plasma adiponectin response to a 2‐hour hyperinsulinemic‐euglycemic clamp. To examine the effects of exercise training, a subgroup of young (<35 years) and aged (>55 years) individuals were randomized into a 12‐week endurance or resistance training programme and had their adiponectin response to hyperinsulinemia measured before and after training. High molecular weight (HMW) and total adiponectin were measured by ELISA. Results: In response to hyperinsulinemia, plasma HMW adiponectin decreased in females (−9%, P  < .005), but not males. After 12 weeks of endurance training, the response of plasma HMW adiponectin to hyperinsulinemia increased in older females (36%, P  < .05) only. Resistance training had no effect on the plasma adiponectin response to hyperinsulinemia. Despite no age or sex differences at baseline, skeletal muscle AdipoR1 increased in response to endurance training (~120%, P  < .001) and resistance training (~38%, P  < .05), regardless of age or sex. Conclusion: The inhibitory action of hyperinsulinemia on plasma HMW adiponectin occurs in females but not males, irrespective of age. Twelve weeks of endurance training protects older females against the hyperinsulinemic inhibition of plasma HMW adiponectin, which could promote healthy ageing.